Proceedings of the 34th International Cosmic Ray Conference — PoS(ICRC2015) 2016
DOI: 10.22323/1.236.0260
|View full text |Cite
|
Sign up to set email alerts
|

Precision Measurement of the Proton Flux in Primary Cosmic Rays from 1 GV to 1.8 TV with the Alpha Magnetic Spectrometer on the International Space Station

Abstract: A precision measurement of the proton flux in primary cosmic rays with rigidity 1 GV to 1.8 TV is presented based on 300 million events. The results show that proton flux is smooth and exhibits no sharp structures with rigidity. The detailed variation with rigidity of the flux spectral index is presented for the first time. The spectral index is progressively hardening at high rigidities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 10 publications
2
9
0
Order By: Relevance
“…The predictions differ slightly because they employ different inputs and different determinations of the uncertainties. However, the qualitative conclu- 2 These measurements are now in very good agreement with the corresponding measurements by PAMELA from 2011 [45,3], after that AMS has revisited its understanding of the systematic errors with respect to the data presented at ICRC 2013 (see footnote 23 of [43]): now both experiments see a spectral break (a.k.a. a 'change of slope') at about 300 GeV.…”
Section: Dark Mattersupporting
confidence: 61%
See 1 more Smart Citation
“…The predictions differ slightly because they employ different inputs and different determinations of the uncertainties. However, the qualitative conclu- 2 These measurements are now in very good agreement with the corresponding measurements by PAMELA from 2011 [45,3], after that AMS has revisited its understanding of the systematic errors with respect to the data presented at ICRC 2013 (see footnote 23 of [43]): now both experiments see a spectral break (a.k.a. a 'change of slope') at about 300 GeV.…”
Section: Dark Mattersupporting
confidence: 61%
“…Indeed, when one includes, in the computations of the predictions from astrophysics, the latest recent developments, the discrepancy is largely reabsorbed. Such latest developments include: (i) the new measurement of the primary proton and Helium spectra (which, impinging on the interstellar medium, produce the bulk of the astrophysical antiprotons), as delivered by AMS itself [43,44] 2 ; (ii) the recent results on the antiproton spallation production cross section [46,48]; (iii) updated propagation schemes [47]. .…”
Section: Dark Mattermentioning
confidence: 99%
“…As shown in Figure 32, we reported a precise measurement of the proton flux in primary cosmic rays with rigidity (momentum/charge) from 1 GV to 1.8 TV based on 300 million events [3]. Knowledge of the rigidity dependence of the proton flux is important in understanding the origin, acceleration and propagation of cosmic rays.…”
Section: Pos(icrc2015)036mentioning
confidence: 99%
“…Anti-deuterons, which are expected to be yet another factor ∼10 −4 below (Chardonnet et al 1997), are still to be detected: the best limit is given by the BESS balloon ; see also Abe et al 2012a for limits on anti-helium), and is still http://lpsc.in2p3.fr/crdb; Contact: crdatabase@lpsc.in2p3.fr three orders of magnitude above what is required to reach the expected astrophysical production. This level could be within reach of the AMS-02 detector on the International Space Station (Arruda et al 2008;Choutko & Giovacchini 2008) and/or the GAPS balloon-borne experiment (Aramaki et al 2012). We note that other milestones in CR studies are the discovery of the γ-ray diffuse emissions that were reported first by Kraushaar et al (1972) and studied by the contemporary Fermi-LAT instrument (Ackermann et al 2012b), and the first evidence of high-energy CRs from extensive air showers (Auger et al 1939), which are currently studied at the Pierre Auger Observatory (e.g., Abraham et al 2010).…”
Section: Introductionmentioning
confidence: 99%